Isoquinoline-derived alkaloids from leaves of Unonopsis stipitata Diels (Annonaceae). (August 2018) - da Silva, Felipe M.A.; da Silva-Filho, Francinaldo A.; de Souza, Cesar Augusto Silva; Maciel, Jessica Burlamaque; Costa, Emmanoel Vilaça; Barison, Andersson; Koolen, Hector H.F.; de Souza, Afonso D.L.; Pinheiro, Maria L.B.
Graphical abstract: Highlights: Six alkaloids were described for the first time in the Unonopsis genus. Seven alkaloids were reported in Unonopsis stipitata for the first time. New substitution patterns were observed for alkaloids in Unonopsis genus. The chemotaxonomic significance of alkaloids for the Unonopsis genus was reinforced.